Monitorization of autophagic flux in a rat model of lung ischemia-reperfusion injury - Insights on organ transplantation surgery - Demir, Tuncer; Bostanciklioglu, Mehmet; Cengiz, Beyhan; Atabey, Husne Didem; Ceribasi, Ali Osman; Bagci, Cahit (Elsevier, 2023)
Ischemia is characterized by cataclysmic oxygen deficiency, but the reperfusion of an ischemic tissue paradox-ically causes more serious damage than the ischemia itself. Ischemia/reperfusion (I/R) triggers organ damage, which is frequently observed in organ transplantation surgery, specifically in heavily blooded organs, such as the lung and kidney. To understand the molecular underpinnings of organ damage in transplant surgery, we aimed to monitor autophagic flux, a cellular death pathway, in an organ transplantation scenario created by prolonged ischemia and reperfusion of the lung. We included a total of 48 adult Wistar-Albino rats weighing 250-300 g in this study. We implemented three different ischemia/reperfusion protocols in three different groups (n = 10) based on different reperfusion times, and we observed one randomly created control group for comparison (n = 10). We then probed the gene expression levels of autophagy mediators in normal and pathologic tissues. Autophagy, a cellular death pathway, is sensitive to intracellular oxidative stress, which is one of the most dramatic markers of reperfused-ischemic tissue. In keeping with this ground, we determined that as the duration of reperfusion increases, autophagy driving proteins, Atg5, Atg7, Atg10, Beclin1, and Ulk1, specifically surge. Reperfusion of an ischemic tissue triggers catastrophic cellular death pathway, autophagy, and thus gives rise to a ruinous result. Considering autophagy inhibitor usage might be prophylactic. We indicated that Atg7 and Atg10 are the most dramatically increased mediators of autophagy. Hence, targeting these mediators with specific agents could increase patient survival and shorten the post-surgical recovery period after transplant surgery.
Keywords: Autophagy; Lung transplantation; Kidney transplantation; Atg7; Atg10; Ischemia/reperfusion